Penicillin resistant pneumococcal peritonitis in nephrotic syndrome. Issue 9 (September 1987) - Milner, L S; Berkowitz, F E; Ngwenya, E; Kala, U; Jacobs, D
Abstract : Two infants with nephrotic syndrome who developed penicillin resistant pneumococcal peritonitis while receiving penicillin chemoprophylaxis are reported and the problems associated with prophylaxis against pneumococcal infection discussed. It is suggested that penicillin prophylaxis may be hazardous in an environment in which penicillin resistant pneumococci are prevalent.